The Role Of Notary In The Implementation Of Credit Agreement And The Default Settlement With Mortgage Right Warranty (A Study At Bank In Pekalongan) - Mochammad Lukman; Atik Noer Chalimah; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Notary is required in a credit agreement which is performed by the bank and its debtor. Problems studied in this research was about the role of Notary in the implementation of Credit Agreement, the factors causing the occurrence of defaults with the guarantee of Mortgage Rights and efforts to settle default disputes with Mortgage Right loan agreement. The method used in this research was with the sociological juridical approach, it was sourced from collecting data obtained from the primary and secondary data, then the data were analyzed by qualitative analysis method. The result of the research are the role of a Notary in the implementation of Credit Agreement is to make the credit agreement requested by the creditor, responsible for the credit document made, and the Notary in charge and responsible to provide guidance and advice to the bank related to the credit documents. Regarding factors causing default with guarantee of Mortgage Rights and settlement of loan defaults is caused by several factors such as internal factor of bank, customer factor and external factor of bank and debtor. The settlement of default is done in 2 options, that is in litigation and non-litigation settlement.Keywords: Credit Agreement; Default; Guarantee; Mortgage Rights.